Phenomenology and Indian philosophy - Chattopadhyaya, D. P. (Debi Prasad), 1933-; Mohanty, Jitendranath, 1928-; Embree, Lester E.; Indian Council of Philosophical Research (New Delhi : Indian Council of Philosophical Research in association with Motilal Banarsidass Publishers, 1992)
Contributed research papers.
Spine title: Phenomenology & Indian philosophy.
Includes bibliographical references and index.
Keywords: Phenomenology